Penguatan Literasi dan Nilai Sosial Anak Melalui Program “Literasi Ceria” di Dusun Dukuh, Sleman, Yogyakarta - Ruhaya, Besse; Nur Aulia N. Lafolaengah; Nur Asizah Apriani Masrul; St. Fatimah Nabilah; Nadiah Sahra Amin; Yultiana; Bungati; Nur Raihan; Siti Farida Afida; Nurwahida; Ade Amy Febrianti; Masnah Abdullah (Faculty of Tarbiyah and Teacher Training, 2026)
Limited engagement in reading activities and the dominance of gadget use during children’s leisure time constituted a non-formal education concern in Dusun Dukuh, Pandowoharjo, Sleman. This community service program aimed to strengthen children’s literacy engagement, creativity, and social values through the Literasi Ceria Program. The program was conducted from 31 July to 30 August 2025 and involved approximately 15–20 primary-school-aged children in each session. A participatory approach was implemented through needs identification, collaborative planning, activity implementation, evaluation, and reflection. The program combined shared reading, storytelling, drawing, coloring, singing, dancing, educational traditional games, and light tutoring. Program achievement was evaluated using observation sheets, a simple parent questionnaire, informal interviews, and documentation, and the data were analyzed descriptively. During the activities, children showed increasingly consistent involvement in taking turns reading, listening to and retelling stories, asking questions, expressing ideas through artwork, cooperating with peers, and following game rules. Parents and community leaders responded positively and considered the program an educational alternative for children’s weekend activities. The program indicated that integrating literacy, arts, traditional games, and learning assistance could create enjoyable community-based learning experiences; however, long-term effects could not be inferred because of the limited implementation period.